Finding of novel lactate utilizing Bacillus sp. YHY22 and its evaluation for polyhydroxybutyrate (PHB) production - Lee, Hong Ju; Kim, Su Gyeong; Cho, Do Hyun; Bhatia, Shashi Kant; Gurav, Ranjit; Yang, Soo Yeon; Yang, Jungwoo; Jeon, Jong Min; Yoon, Jeong Jun; Choi, Kwon Young; Yang, Yung Hun (International Journal of Biological Macromolecules, 2022)
Polyhydroxyalkanoates (PHAs) and their derivatives are biopolymers that have the potential of replacing petroleum-based plastics and can be produced and degraded via bacterial metabolism. However, there are only a few studies on polyhydroxybutyrate (PHB) production using lactate, one of the major waste organic acids that could be implemented in the production of polylactic acid (PLA). Herein, we screened and characterized the PHA-producing microbial strains isolated from saltern soil from Docho Island (South Korea). Among the 24 identified microorganisms that can use lactate as a carbon source, Bacillus sp. YHY22, a newly reported strain, produced the highest amount of PHB: 4.05 g/L with 6.25 g/L dry cell weight, which is 64.7% PHB content under optimal production conditions. Bacillus sp. YHY22 could form the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer with propionate addition. Moreover, Bacillus sp. YHY22 produced PHB in non-sterilized 2% lactate and 8% NaCl marine broth culture medium, suggesting that its production can occur in high salinity media without additional sterilization steps, rendering fermentation cost- and time-efficient.
Keywords: Bacillus; Biopolymers; Hydroxybutyrates; Lactic Acid; Polyesters; Polyhydroxyalkanoates; Bacillus sp. YHY22; Lactate; Polyhydroxyalkanoate